Peningkatan Pemahaman Konsep Matematika melalui Pendekatan Etnomatematika Berbasis Kebudayaan Kudus Kelas I Sekolah Dasar - Amanina, Syahida Asma; Ermawati, Diana; Khairunisa, Imada (YASIN, 2025)
Understanding basic mathematical concepts at the elementary school level plays an important role as a foundation for students in solving mathematical problems. Current mathematics learning still emphasizes conventional lecture methods, causing many students to struggle with internalizing mathematical concepts. One innovation that can be applied is the ethnomathematics approach, which links mathematical concepts with local culture. This study aims to determine the improvement in understanding mathematical concepts through a culture-based ethnomathematics approach in Grade I at SDN Demangan. The research was conducted in two cycles of Classroom Action Research (CAR) using the Kemmis & McTaggart model. The subjects of the study consisted of 4 male students and 1 female student. Data were collected from the results of the mathematical concept understanding tests and analyzed descriptively. The results indicate an increase in the percentage of completeness from 20% in the pre-cycle to 40% in Cycle I, and further increased to 80% in Cycle II. These findings suggest an improvement in understanding mathematical concepts through the culture-based ethnomathematics approach in Kudus.